Gender Differences in Generating Cognitive Reappraisals for Threatening Situations: Reappraisal Capacity Shields Against Depressive Symptoms in Men, but Not Women - Perchtold, Corinna M.; Papousek, Ilona; Fink, Andreas; Weber, Hannelore; Rominger, Christian; Weiss, Elisabeth M. (Frontiers in Psychology, 2019)
Despite major research interest regarding gender differences in emotion regulation, it is still not clear whether men and women differ in their basic capacity to implement specific emotion regulation strategies, as opposed to indications of the habitual use of these strategies in self-reports. Similarly, little is known on how such basic capacities relate to indices of well-being in both sexes. This study took a novel approach by investigating gender differences in the capacity for generating cognitive reappraisals in adverse situations in a sample of 67 female and 59 male students, using a maximum performance test of the inventiveness in generating reappraisals. Participants’ self-perceived efficacy in emotion regulation was additionally assessed. Analyses showed that men and women did not differ in their basic capacity to generate alternative appraisals for anxiety-eliciting scenarios, suggesting similar functional cognitive mechanisms in the implementation of this strategy. Yet, higher cognitive reappraisal capacity predicted fewer depressive daily-life experiences in men only. These findings suggest that in the case of cognitive reappraisal, benefits for well-being in women might depend on a more complex combination of basic ability, habits, and efficacy-beliefs, along with the use of other emotion regulation strategies. The results of this study may have useful implications for psychotherapy research and practice.